2014
DOI: 10.1161/strokeaha.114.005202
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Plaque in the Left Carotid Artery Is More Vulnerable Than in the Right

Abstract: Background and Purpose-Ischemic stroke is more often diagnosed in the left hemisphere than in the right. It is unknown whether this asymmetrical prevalence relates to differences in carotid atherosclerosis. We compared atherosclerotic plaque prevalence, severity, and composition between left and right carotid arteries. Methods-In a population-based cohort, carotid MRI scanning was performed in 1414 stroke-free participants (≥45 years).Using a multisequence MRI protocol, we assessed the prevalence, stenosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 38 publications
(42 reference statements)
3
62
1
3
Order By: Relevance
“…[17] Studies comparing atherosclerosis between left and right carotid arteries are sparse. [27,28] In 50 pairs of carotid arteries from cadavers, total wall volumes on MRI of left and right carotid arteries were correlated. [28] We confirmed these findings in vivo in a more clinically relevant cohort of high-risk atherosclerotic patients and extended the observation to include not only plaque size but composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Studies comparing atherosclerosis between left and right carotid arteries are sparse. [27,28] In 50 pairs of carotid arteries from cadavers, total wall volumes on MRI of left and right carotid arteries were correlated. [28] We confirmed these findings in vivo in a more clinically relevant cohort of high-risk atherosclerotic patients and extended the observation to include not only plaque size but composition.…”
Section: Discussionmentioning
confidence: 99%
“…In the Rotterdam study the prevalence, severity and composition of left and right carotid arteries were assessed using non-contrast MRI in stroke-free population. [27] Bilateral atherosclerotic plaques were identified in most individuals (85%) reflecting the systemic nature of atherosclerosis. With emerging new lipid lowering drugs like PCSK9 inhibitors,[29,30] identifying a group of patients with lipid-rich plaques may offer a potential targeted indication for these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…While it is commonly accepted that coronary and carotid artery atherosclerosis are related, subtle differences in disease characteristics, including pharmacotherapy effects, have been observed. 50 Within the carotid arteries there are reports of site-specific plaque progression rates 51,52 and subsequent clinical events. 53 Furthermore, the right and left carotid arteries have different anatomic origins which may affect local hemodynamics forces, a known contributor to carotid artery plaque localization and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been obtained in other studies 6,9,13,26,28) , although some studies found no association between cIMT and HOMA-IR 30,31) . Various studies have demonstrated discrepancies between the intima-media thicknesses measured on the left and right common carotid arteries 32) and emphasized the importance of measuring and reporting values from both sides when conducting cIMT studies [33][34][35] . Atherosclerotic lesions may develop earlier on the left side than the right side because of the anatomical configuration of the left carotid artery, which originates directly from the aortic arch and, therefore, may be exposed to greater shear stress than the right carotid artery.…”
Section: Discussionmentioning
confidence: 99%